Intelligence-Sharing Agreements & International Data Protection: Avoiding a Global Surveillance State - Rachel C. Taylor (Washington University Global Studies Law Review, 2018)
International threats to national security have resulted in a coordinated response among states to protect their citizens, but in a post-Snowden world, are states also protecting the data integrity of its citizens? Intelligence-sharing agreements’ opacity undermine public trust given the revelations of unchecked government surveillance that emerged in 2013. The Five Eyes agreement, perhaps the most famous and fundamental promise amongst US allies, remains shrouded in mystery despite the public demand for less intrusive and more translucent government surveillance practices. This agreement and those which mirror it evade the few domestic safeguards that serve to ensure democratic surveillance. Taking a lesson from European courts’ skepticism of Five Eyes nations’ surveillance practices, this note urges American legislators and judges to favor democratic accountability over executive deference.
Keywords: intelligence sharing agreements; international data; data protection; global surveillance; privacy; privacy law